UJI EFEK ANTIINFLAMASI DARI EKSTRAK ETANOL DAUN AWAR AWAR (Ficus septica Burm L. ) TERHADAP TIKUS PUTIH (Rattus norvegicus) YANG DIINDUKSI KARAGEN - Rahmadani, Andi Syafirah; Asmaliani, Ira; Santi, Irma; Sukmawati, Sukmawati; Kosman, Rachmat; Herman, Hendra (As-Syifaa Jurnal Farmasi, 2024)
Inflammation occurs as a normal protective response to tissue damage caused by physical trauma, harmful chemicals, or microbiological substances. Awar-awar leaves contain flavonoid compounds with anti-inflammatory properties, as they can inhibit cyclooxygenase or lipoxygenase enzymes and prevent the accumulation of leukocytes, thereby reducing the inflammatory response. This study aims to determine the effect and effective dose of ethanol extract from awar-awar leaves (Ficus septica Burm L.) as an anti-inflammatory agent in white rats (Rattus norvegicus). The research involved 25 male white rats divided into five treatment groups: Group I received Na-CMC, Group II received 50 mg Diclofenac Sodium, and Groups III, IV, and V received ethanol extract of awar-awar leaves (Ficus septica Burm L.) at doses of 100, 200, and 400 mg/kgBW, respectively. The results showed that the ethanol extract of awar-awar leaves at a dose of 200 mg/kgBW had the most effective anti-inflammatory effect in reducing the volume and diameter of edema in male rats